1992
DOI: 10.1007/bf00129087
|View full text |Cite
|
Sign up to set email alerts
|

Transformations of ammonia and the environmental impact of nitrifying bacteria

Abstract: In the sequence of events leading from ammonia to N2 during the process of biotransformation of inorganic nitrogen compounds, the weakest link, with respect to our knowledge and understanding of the organisms involved, is nitrification. In particular, this is true for the oxidation of ammonia to nitrite. The enzymes have not been thoroughly studied, and the enzymatic mechanisms have not been identified. Almost any biochemical and physiological aspect studied proved to be controversial, and major ecological que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…The only known pathway to gain energy was assumed to be aerobic oxidation of ammonia to nitrite. However, the appearance of aerobic nitrifiers in anoxic environments [1,2] indicated that AOB are more versatile than previously assumed. It was discovered that Nitrosomonas eutropha could also use nitrite as electron acceptor, which was observed under three conditions: (i) hydrogen-dependent denitrification, (ii) anoxic ammonia oxidation with NO 2 [3] and (iii) NO x -induced aerobic ammonia oxidation.…”
Section: Introductionmentioning
confidence: 81%
“…The only known pathway to gain energy was assumed to be aerobic oxidation of ammonia to nitrite. However, the appearance of aerobic nitrifiers in anoxic environments [1,2] indicated that AOB are more versatile than previously assumed. It was discovered that Nitrosomonas eutropha could also use nitrite as electron acceptor, which was observed under three conditions: (i) hydrogen-dependent denitrification, (ii) anoxic ammonia oxidation with NO 2 [3] and (iii) NO x -induced aerobic ammonia oxidation.…”
Section: Introductionmentioning
confidence: 81%
“…The quantitative and qualitative biases can be avoided by the use of in situ techniques. The fluorescent antibody (FA) technique has been developed to overcome the limitations with culture dependent methods (Abeliovich 1992). In this technique, antibodies were labelled to detect the targeted organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Another environmental factor believed to have a detrimental effect on nitrification is sunlight. In wastewater reservoirs during summer months, a phenomenon of unbalanced nitrification frequently is observed, leading to accumulation of nitrite (Abeliovich, 1992). However, the increase of nitrification observed during the higher solar radiation periods (mean values of approximately 200 6 70 W/m 2 for the period June through August during both summers 2009 and 2010) and the absence of nitrite accumulation indicated that light was not a major inhibiting factor in our pond system, in contrast to what was reported for a wastewater reservoir in Israel (Kaplan et al, 2000).…”
Section: Resultsmentioning
confidence: 99%